HUBUNGAN TINGKAT KECEMASAN LANSIA DENGAN KESIAPAN PEMBERIAN VAKSINASI COVID-19 DI NAGARI AIA TAJUN KECAMATAN LUBUK ALUNG - Helman Pelani; Henniwati Henniwati; Hega Valentine (Ensiklopedia Education Review, 2022)
Coronaviruses are a large family of viruses that cause disease in humans and animals. In humans, it usually causes respiratory tract infections, ranging from the common cold to serious diseases such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). Vaccination is the administration of vaccines in order to actively generate or increase a person's immunity against certain diseases, so that if one day a certain disease will not get sick or experience mild illness and will not become a source of transmission. This study aims to determine the "Relationship of Anxiety Levels in the Elderly with Readiness to Give Covid-19 Vaccination in Nagari Aia Tajun, Lubuk Alung District".This type of research is an analytic survey using the "Cros Sectional Study" research design which is a study in which the anxiety level variable and the dependent variable are Covid-19 Vaccination Readiness. In this study, the sampling technique used was population based, by using non-probability sampling with purposive sampling method with a minimum sample of 30 people in Nagari Aia Tajun, Lubuk Alung District.The results showed that the elderly who experienced normal anxiety who were not ready for vaccination were 7 people (6.3%) and 21 people were ready for the vaccine (21.7%). For anxiety who are not ready to be vaccinated as many as 2 people (2.7%) and 10 people (9.3%) are ready for Covid-19 vaccination. results Based on statistical tests using cross tabulation using the chi-square test, the p value = 0.563 (p value < 0.05).So it can be concluded, there is no significant relationship between the level of anxiety of the elderly against the administration of Covid-19 vaccination in the elderly Nagari Aia Tajun, Lubuk Alung District.